Thirty-Day Mortality for Proximal Femoral Fractures Treated at a U.K. Elective Center with a Site-Streaming Policy During the COVID-19 Pandemic - A. Beaven, MRCS (Wolters Kluwer, 2021)
Background:. COVID-19 led to the reconfiguration of U.K. orthopaedic trauma services because surgical capacity was threatened in acute centers. We report the 30-day mortality of proximal femoral fractures in older adults treated at an elective orthopaedic center. Methods:. Patients >60 years old who presented with a proximal femoral fracture to any of 4 sites in the regional trauma network were transferred to our elective center for emergency surgery. Care was modeled according to the National Institute for Health and Care Excellence guidelines, and efforts were made to treat all patients within 36 hours. Data were collected prospectively, and mortality outcomes were recorded. Results:. Of the 192 patients who presented to the elective orthopaedic center, 167 were treated there. The median age of the latter patients was 88 years (interquartile range, 83 to 79 years). The median Charlson Comorbidity Index was 4 (interquartile range, 4 to 6). The median time from emergency department admission to surgical treatment was 24.5 hours (interquartile range, 18.8 to 34.7 hours). The 30-day rate of mortality was 10.2%. A total of 29 (17.4%) tested positive for COVID-19 during their admission, of whom 10 died, for a case-fatality rate of 34.5%. There were no significant differences in age (p = 0.33) or Charlson Comorbidity Index (p = 0.13) between patients who tested positive and those who did not. There was no significant difference in age between those who tested positive and died and those who tested positive and did not die (p = 0.13), but there was a significant difference in Charlson Comorbidity Index between those subgroups (p = 0.03). Conclusions:. During a pandemic, an elective orthopaedic center can be reconfigured to a surgical center for older patients with proximal femoral fractures with acceptable health-care quality outcomes. Level of Evidence:. Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.